Kernels in Mycielskian of a Digraph - Lakshmi, R; Vidhyapriya, S (International Journal of Computer Sciences and Engineering, 2019)
A kernel of a digraph is an independent set of vertices of such that for every vertex there exists an arc from to a vertex in The Mycielskian of a digraph is the digraph with vertex set where and the arc set In this paper, we have proved that, for any digraph D, the Mycielskian of contains a kernel.